Pengaruh E-LKPD Berbasis Etnomatematika Permainan Tradisional Congklak terhadap Kemampuan Numerasi Operasi Pengurangan di Kelas II SD - Nabila Setyawati; Dian Kusmaharti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy ability is one of the essential competencies that elementary school students must develop, particularly in understanding basic arithmetic operations such as subtraction. However, many second-grade students still experience difficulties in comprehending subtraction concepts due to abstract learning processes, limited contextual learning experiences, and the lack of engaging instructional media. This study aimed to determine the effect of ethnomathematics-based electronic student worksheets (E-LKPD) integrated with the traditional congklak game on students’ numeracy ability in subtraction operations. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of second-grade elementary school students divided into an experimental group and a control group. The experimental group received instruction using ethnomathematics-based E-LKPD through the traditional congklak game, while the control group received conventional instruction. Data were collected through numeracy tests (pretest and posttest) and classroom observations. The data were analyzed using SPSS through normality, homogeneity, and independent sample t-tests. The findings revealed a significant effect of the ethnomathematics-based E-LKPD on students’ numeracy ability in subtraction operations. Students in the experimental group demonstrated higher improvement in numeracy performance compared to those in the control group. The integration of digital interactive worksheets with cultural learning contexts enhanced student engagement, facilitated conceptual understanding, and created a more meaningful learning experience. Therefore, ethnomathematics-based E-LKPD utilizing the traditional congklak game can be considered an effective alternative instructional medium for improving numeracy skills among second-grade elementary school students